A Technological Review of the Instrumented Footwear for Rehabilitation with a Focus on Parkinson’s Disease Patients - Maculewicz, Justyna; Kofoed, Lise Busk; Serafin, Stefania (Frontiers in Neurology, 2016)
In this review article, we summarize systems for gait rehabilitation based on instrumented footwear and present a context of their usage in Parkinson’s disease (PD) patients’ auditory and haptic rehabilitation. We focus on the needs of PD patients, but since only a few systems were made with this purpose, we go through several applications used in different scenarios when gait detection and rehabilitation are considered. We present developments of the designs, possible improvements, and software challenges and requirements. We conclude that in order to build successful systems for PD patients’ gait rehabilitation, technological solutions from several studies have to be applied and combined with knowledge from auditory and haptic cueing.